A Microporous Hydrogen Bonded Organic Framework for Highly Selective Separation of Carbon Dioxide over Acetylene - Li, Yunbin; Wang, Xue; Zhang, Hao; He, Lei; Huang, Jiali; Wei, Wuji; Yuan, Zhen; Xiong, Zhile; Chen, Huadan; Xiang, Shengchang; Chen, Banglin; Zhang, Zhangjing (Angewandte Chemie International Edition, 2023)
The separation of acetylene (C2H2) from carbon dioxide (CO2) is a very important but challenging task due to their similar molecular dimensions and physical properties. In terms of porous adsorbents for this separation, the CO2‐selective porous materials are superior to the C2H2‐selective ones because of the cost‐ and energy‐efficiency but have been rarely achieved. Herein we report our unexpected discovery of the first hydrogen bonded organic framework (HOF) constructed from a simple organic linker 2,4,6‐tri(1H‐pyrazol‐4‐yl)pyridine (PYTPZ) (termed as HOF‐FJU‐88) as the highly CO2‐selective porous material. HOF‐FJU‐88 is a two‐dimensional HOFs with a pore pocket of about 7.6 Å. The activated HOF‐FJU‐88 takes up a high amount of CO2 (59.6 cm3 g−1) at ambient conditions with the record IAST selectivity of 1894. Its high performance for the CO2/C2H2 separation has been further confirmed through breakthrough experiments, in situ diffuse reflectance infrared spectroscopy and molecular simulations. The novel two‐dimensional ultramicroporous hydrogen‐bonded organic framework (HOF), denoted as HOF‐FJU‐88, is synthesized utilizing the organic linker 2,4,6‐tri(1H‐pyrazol‐4‐yl)pyridine. Once activated, HOF‐FJU‐88 demonstrates a notable selectivity for CO2 over C2H2 with an IAST selectivity index of 1894.